Case Report: A Case of Pituitary Carcinoma Treated With Sequential Dual Immunotherapy and Vascular Endothelial Growth Factor Inhibition Therapy - Lamb, Lydia S.; Sim, Hao-Wen; McCormack, Ann I. (Frontiers in Endocrinology, 2020)
Aggressive pituitary tumors (APTs) are associated with significant morbidity and mortality and effective treatment options are limited. Immune checkpoint inhibitors (ICIs) have revolutionized clinical cancer care however there is little experience with these agents in the management of APTs. Vascular endothelial growth factor (VEGF) targeted therapy has reported success in a small number of APT case reports. Here we describe a case of pituitary carcinoma responding to ICI therapy and subsequently VEGF inhibition. We discuss the possible mechanisms and experience with ICI therapy and VEGF inhibitors in the management of APTs, biomarkers that may predict response and the potential role of combination therapies including ICIs and temozolomide.